STUDENTS’ LEVEL OF SPEAKING ANXIETY OF THE THIRD SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF FKIP UKI TORAJA - Yizar Pakiding; Sushy Teko Patanduk; Aris Kaban Sendana (Publikasi dan UKI Press UKI Toraja., 2023)
The purpose of this research is to find the level of speaking anxiety of the third semester students’ of English education study program FKIP UKI Toraja. In analyzing the data of this research, the researcher employed quantitative method. The subject of this research were the third semester students’ of English education study program FKIP UKI Toraja. The data of this research was collected by questionnaire. The obtained data were analyzed using likert scale techniques to analyze data. The results of the research indicate that speaking anxiety is experienced by most students. The data obtained from the positive statement is 66,5% and from the negative statement is 65,9%. The mean score of the data is 66,2%. Based on the result of this study the researcher concluded that the level of speaking anxiety of the students’ was on medium anxiety